Prospective Observational Evaluation of Time‐Dependency of Adalimumab Immunogenicity and drug concentrations: the POETIC Study. (June 2018) - Ungar, Bella; Engel, Tal; Yablecovitch, Doron; Lahat, Adi; Lang, Alon; Avidan, Benjamin; Har‐Noy, Ofir; Carter, Dan; Levhar, Nina; Selinger, Limor; Neuman, Sandra; Natour, Ola Haj; et al.
Abstract : OBJECTIVES: Adalimumab is usually self‐injected at home, making prospective serial‐sampling studies challenging and scarce. This has led to a gap in knowledge about evolution of anti‐adalimumab antibodies (AAAs) over time and its correlation with clinical and inflammatory outcomes. METHODS: A program for home visits by physicians at induction, every 3 months and at event of relapse, was established prospectively for Crohn's disease (CD) patients. At each visit, patients' clinical scores were determined and sera were obtained for C‐reactive protein, drug, and AAA levels. This cohort was compared to a parallel prospective cohort of infliximab‐treated CD patients. In a subgroup of 29 patients, trough and in‐between‐trough levels were compared, to elucidate the importance of timing of sampling during the injection cycle. RESULTS: Ninety‐eight CD patients starting adalimumab were prospectively followed (median follow‐up 44 weeks) and 621 serum samples were analyzed. Thirty‐three patients (32%) developed AAA; 18/33 (55%) of them as early as week 2, and 26/33 (79%) by week 14. Induction period AAAs were strongly associated with primary non‐response (odds ratio (OR) = 5.4, 95% confidence interval (CI): 1.6–17.8, p = 0.005). As compared to antibodies‐to‐infliximab (ATI), AAA formation rate over time was significantly lower ( p = 0.01) and AAA were much more specific—85% of AAA events were associated with loss‐of‐response compared with 58% rate for ATI ( p = 0.01). In 29 patients sampled serially during an injection cycle, levels of drug and AAA seemed comparable between four time‐points during a single cycle both in patients with or without AAA ( n = 8, n = 21, respectively). CONCLUSIONS: When followed prospectively and serially, AAAs are found to arise earlier than previously appreciated and their impact may be more pronounced for primary rather than secondary, non‐response. Drug and AAA levels were similar both at trough and in‐between injections, enabling to simplify therapeutic drug monitoring of adalimumab. SUPPLEMENTARY MATERIAL accompanies this paper at https://doi.org/10.1038/s41395–018–0073–0